Is it time to reassess current safety standards for glyphosate-based herbicides?. Issue 6 (20th March 2017) - Vandenberg, Laura N; Blumberg, Bruce; Antoniou, Michael N; Benbrook, Charles M; Carroll, Lynn; Colborn, Theo; Everett, Lorne G; Hansen, Michael; Landrigan, Philip J; Lanphear, Bruce P; Mesnage, Robin; vom Saal, Frederick S; et al.
Abstract : Use of glyphosate-based herbicides (GBHs) increased ∼100-fold from 1974 to 2014. Additional increases are expected due to widespread emergence of glyphosate-resistant weeds, increased application of GBHs, and preharvest uses of GBHs as desiccants. Current safety assessments rely heavily on studies conducted over 30 years ago. We have considered information on GBH use, exposures, mechanisms of action, toxicity and epidemiology. Human exposures to glyphosate are rising, and a number of in vitro and in vivo studies challenge the basis for the current safety assessment of glyphosate and GBHs. We conclude that current safety standards for GBHs are outdated and may fail to protect public health or the environment. To improve safety standards, the following are urgently needed: (1) human biomonitoring for glyphosate and its metabolites; (2) prioritisation of glyphosate and GBHs for hazard assessments, including toxicological studies that use state-of-the-art approaches; (3) epidemiological studies, especially of occupationally exposed agricultural workers, pregnant women and their children and (4) evaluations of GBHs in commercially used formulations, recognising that herbicide mixtures likely have effects that are not predicted by studying glyphosate alone.